Yu-Gi-Oh! Zexal. Vol. 9: Yuma Jets!! - Yoshida, Shin; Takahashi, Kazuki, 1961-; Engel, Taylor; Reid, Ian (Translator) (VIZ Media, LLC, 2016)
With the deity of despair announcing her intent to destroy the Astral World, Yuma, Kaito, Shark, and Astral grab their D-Gazers and begin an epic duel that will decide the fate of the universe.